2022
DOI: 10.1101/2022.08.05.502758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative pathogenicity of SARS-CoV-2 Omicron subvariants including BA.1, BA.2, and BA.5

Abstract: Unremitting emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants imposes us to continuous control measurement. Given the rapid spread, new Omicron subvariant named BA.5 is urgently required for characterization. Here we analyzed BA.5 with the other Omicron variants BA.1, BA.2, and ancestral B.1.1 comprehensively. Although in vitro growth kinetics of BA.5 is comparable among the Omicron subvariants, BA.5 become much more fusogenic than BA.1 and BA.2. The airway-on-a-chip analysis s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(95 citation statements)
references
References 39 publications
(66 reference statements)
3
71
0
Order By: Relevance
“…To evaluate the sensitivity of BA.2.75 to three antiviral drugs, Remdesivir, EIDD-1931 (an active metabolite of Molnupiravir) and Nirmatrelvir (also known as PF-07321332), we used a clinical isolate of BA.2.75 (strain TY41-716; GISAID ID: EPI_ISL_13969765). As controls, we also used clinical isolates of B.1.1 (strain TKYE610670; GISAID ID: EPI_ISL_479681) (Suzuki et al ., 2022), BA.2 (strain TY40-385; GISAID ID: EPI_ISL_9595859) (Kimura et al ., 2022c), BA.5 (strain TKYS14631; GISAID ID: EPI_ISL_12812500) (Tamura et al, 2022). These viruses were inoculated into human airway organoids (AO), a physiologically relevant model (Sano et al, 2022), and treated with three antiviral drugs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the sensitivity of BA.2.75 to three antiviral drugs, Remdesivir, EIDD-1931 (an active metabolite of Molnupiravir) and Nirmatrelvir (also known as PF-07321332), we used a clinical isolate of BA.2.75 (strain TY41-716; GISAID ID: EPI_ISL_13969765). As controls, we also used clinical isolates of B.1.1 (strain TKYE610670; GISAID ID: EPI_ISL_479681) (Suzuki et al ., 2022), BA.2 (strain TY40-385; GISAID ID: EPI_ISL_9595859) (Kimura et al ., 2022c), BA.5 (strain TKYS14631; GISAID ID: EPI_ISL_12812500) (Tamura et al, 2022). These viruses were inoculated into human airway organoids (AO), a physiologically relevant model (Sano et al, 2022), and treated with three antiviral drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Here we revealed that both BA.5 and BA.2.75 are more fusogenic than BA.2 in the in vitro cell culture systems ( Figures 3 and 4 ). Given that the recombinant SARS-CoV-2 bearing the BA.5 S (Kimura et al ., 2022c) as well as a clinical isolate of BA.5 (Tamura et al ., 2022) exhibited relatively higher pathogenicity than BA.2 in hamsters, it is hypothesized that BA.2.75 is also intrinsically more pathogenic than BA.2. To address this possibility, we intranasally inoculated a BA.2.75 isolate into hamsters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations